Factors associated the worsening of symptoms and quality of life in women with urinary - Guedes, Priscilla Fonseca; Marques, Clandio Timm; Frigo, Leticia Fernandez; de Jesus, Sibila Reck; da Rocha, João Batista Teixeira; Colpo, Elisângela (Disciplinarum Scientia | Saúde, 2022)
Introduction: Urinary incontinence (UI) greatly affects the quality of life of women. Consumption of citrus fruits and caffeine may worsen symptoms of incontinence. The objective was to determine risk factors associated with incontinence, assess quality and life, as well as verify whether caffeine and ascorbic acid worsen the symptoms of incontinent women. Materials and methods: A cross-sectional study was carried out at a basic health unit in Santa Maria/RS, with 43 women, 20 with symptoms of UI and 23 without UI. We investigated risk factors such as socioeconomic profile, type of delivery, nutritional status and eating habits, as well as quality of life. Results: Socioeconomic data were not statistically different in both groups. We observed a significant association of multiparity and vaginal delivery with UI. The quality of life of the incontinent participants was lower in comparison to the continent women. We analyzed the impact of incontinence symptoms and classified them as mild and severe. We observed that caffeine consumption was not statistically different in women with mild or severe incontinence. Women with severe symptoms consume more citrus fruits, but this did not influence the worsening of symptoms. Also, we observed that incontinent women have a lower water consumption than the continents. Conclusion: The ingestion of caffeinated and citrus foods is not associated with the severity of the disease. UI can influence quality of life, so we suggest that incontinent women maintain good eating and adequate water consumption habits in order to have a better quality of life.